Comparison of Sensory Descriptive Flavor Profiles Between Cooked Hot-boned and Cold-deboned Broiler Breast Fillets - Zhuang , Hong; Savage, Elizabeth M. (International Journal of Poultry Science, 2011)
Three trials were conducted to compare sensory descriptive flavor profiles of cooked broiler breast fillets (pectoralis major) that were either hot-boned or cold-deboned postmortem. Broiler carcasses were hot-boned (about 45 min postmortem) and cold-deboned 2 h postmortem (2 h) and 24 h postmortem (24 h). Descriptive sensory flavor as well as texture attributes were evaluated by 8 trained descriptive panelists using 0-15 universal intensity scales. There were no significant differences in average sensory descriptive flavor intensity scores between hot-boned and 2 h fillets. However, the average score of 24 h samples for the flavor attribute cardboardy was significantly lower than hot-boned fillets and was not different from 2 h fillets and the score for the attribute sweet was significantly higher than hot-boned and 2 h samples. These results indicate that sensory descriptive flavor profiles of cooked hot-boned and 2 h broiler fillets are similar to each other. However, cooked 24 h fillets have different sensory descriptive flavor profiles from either hot-boned or 2 h fillets.